Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Central North Slope, Alaska - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the ThawTrend-Air airborne campaign led by the Alfred Wegener Institute in 2019, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 10 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates four data subsets of the central North Slope, Alaska, covering approximately 55 km². All images were collected on 29 July 2019.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion